The role of compliance in the treatment of tuberculosis patients - Mamatova, Nargiza Toirjonovna; Abdukhakimov, Bakhrombek Abduvaliyevich; Akhtamova, Shirin Khayrulloevna; Ashurov, Abduvaliy Abdukhakimovich (Science and Education, 2024)
Compliance is an essential factor in the success of treatment for tuberculosis patients receiving inpatient care, as the attitude towards therapy, confidence in the attending doctor, and overall emotional state directly affect the quality and rate of recovery. The question arises about the need for psychological support of the treatment process in phthisiology, which, according to the results obtained, is virtually absent. It seems that the key role in such interaction should be played by a medical (clinical) psychologist, and the key determinants of the focus of his work will be increasing patient compliance and correcting stigmatizing manifestations in doctors.